2016
DOI: 10.1111/jcpt.12403
|View full text |Cite
|
Sign up to set email alerts
|

Decreased INR after acenocoumarol, ombitasvir/paritaprevir/ritonavir and dasabuvir co-administration

Abstract: Because of possible INR abnormalities during the concomitant use of acenocoumarol, ombitasvir/paritaprevir/ritonavir and dasabuvir, clinicians should closely monitor INR values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…Some interactions are easy to manage (monitoring blood pressure), whereas others are highly complex due to the metabolic profile of the DAAs and the CVD (e.g., clopidogrel). This is, for instance, reported by de Lorenzo-Pinto et al [ 11 ], who reported a significantly increased acenocoumarol dose because of the interaction with paritraprevir/ritonavir, ombitasvir, and dasabuvir (PrOD). Comparable interaction was seen with warfarin, resulting in a subtherapeutic international normalized ratio (INR) during concomitant treatment with PrOD [ 11 ].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some interactions are easy to manage (monitoring blood pressure), whereas others are highly complex due to the metabolic profile of the DAAs and the CVD (e.g., clopidogrel). This is, for instance, reported by de Lorenzo-Pinto et al [ 11 ], who reported a significantly increased acenocoumarol dose because of the interaction with paritraprevir/ritonavir, ombitasvir, and dasabuvir (PrOD). Comparable interaction was seen with warfarin, resulting in a subtherapeutic international normalized ratio (INR) during concomitant treatment with PrOD [ 11 ].…”
Section: Introductionsupporting
confidence: 54%
“…This is, for instance, reported by de Lorenzo-Pinto et al [ 11 ], who reported a significantly increased acenocoumarol dose because of the interaction with paritraprevir/ritonavir, ombitasvir, and dasabuvir (PrOD). Comparable interaction was seen with warfarin, resulting in a subtherapeutic international normalized ratio (INR) during concomitant treatment with PrOD [ 11 ]. Both of these cases showed that there were significant DDIs between anticoagulants and PrOD, making increased monitoring necessary.…”
Section: Introductionsupporting
confidence: 54%
“…To our knowledge, no case reports of a drug interaction between warfarin and LDV/SOF have been published, although there have been reports of interactions with OBV/PTV/r + DSV and first‐generation DAAs . Patients in our case series required increased warfarin doses after beginning HCV treatment, and two patients subsequently required a dose reduction at the end of treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Patients in our case series required increased warfarin doses after beginning HCV treatment, and two patients subsequently required a dose reduction at the end of treatment. Case reports have previously described a suspected interaction between warfarin and the following regimens: IFN + RBV; PEG‐IFN + RBV + telaprevir; PEG‐IFN + RBV + boceprevir; and OBV/PTV/r with DSV + RBV . These cases reported warfarin dose increases ranging from 39–137% in the weeks following initiation of HCV treatment to maintain therapeutic INR, followed by dose reductions of 21–24% following HCV treatment completion …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation